2023
DOI: 10.55730/1300-0144.5662
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of children diagnosed with Kawasaki disease

FATİH VAROL,
REYHAN DEDEOĞLU,
AZİZ KILIÇ
et al.

Abstract: Background/aim The aim of our study was to evaluate the long-term impacts of Kawasaki disease on our patients regarding coronary involvement demographic characteristics, treatment regimens, and clinical course. Materials and methods Our study included 104 patients diagnosed and hospitalized with Kawasaki disease in our center, from January 2004 to January 2019. In our study, patients were divided into three groups according to coronary artery involvement. Patients in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…About 10–20% of patients with KD are nonresponsive to IVIGs, requiring secondary treatments, and may display an increased risk of CVAs: their early identification is critical to reinforce the standard initial approach to such patients, but all available scoring systems are unsuitable in non-Japanese populations [ 15 ]. We previously found that higher CRP values and younger age at KD onset were associated, respectively, with a failure in IVIG response and a higher risk of CVAs [ 16 ]. Additionally, the exact risk of developing cardiovascular events after KD remains undefined, warranting preventive counseling and regular cardiovascular surveillance in all children with a history of previous KD, aiming to mitigate the risk of eventual adult-onset cardiovascular diseases [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 10–20% of patients with KD are nonresponsive to IVIGs, requiring secondary treatments, and may display an increased risk of CVAs: their early identification is critical to reinforce the standard initial approach to such patients, but all available scoring systems are unsuitable in non-Japanese populations [ 15 ]. We previously found that higher CRP values and younger age at KD onset were associated, respectively, with a failure in IVIG response and a higher risk of CVAs [ 16 ]. Additionally, the exact risk of developing cardiovascular events after KD remains undefined, warranting preventive counseling and regular cardiovascular surveillance in all children with a history of previous KD, aiming to mitigate the risk of eventual adult-onset cardiovascular diseases [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not established a clear correlation between desquamation, coronary anomalies, and thrombocytosis with coronary anomalies. Some papers have reported no association, while others suggest that more severe desquamation may correlate with fewer coronary complications, and increased thrombocytosis may be associated with a higher incidence of coronary complications ( 6 , 10 , 24 , 25 , 34 ). Our study has limitations in discussing the correlation between desquamation, thrombocytosis and coronary artery complications, and the outcomes of early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound findings of typical coronary artery abnormalities are also an important indicator for diagnosing KD, but CAL tends to be delayed, which makes diagnosing KD with ultrasound lagging behind, and the optimal window of time for initial IVIG therapy in KD is within 10 days of onset, with delayed treatment leading to increased risk of drug resistance and CALs (8,9). A recent study in Turkey also showed that prolonged duration of IVIG treatment is the most important determinant of the occurrence of CAL (10). Therefore, in order to avoid underdiagnosis and misdiagnosis of KD, new diagnostic markers should be actively developed on the basis of clinical presentation and cardiac ultrasound.…”
Section: Introductionmentioning
confidence: 99%